Der Bundespräsident. Briefe 1949-1954 - Heuss, Theodor (Briefe, 2012)
Already in his first term of office Theodor Heuss laid the foundation for a new tradition in German history. In his person, a positive attitude towards democracy was uniquely united with extensive historical experience and a strong political will to shape the young state. Through his educated but at the same time folksy demeanor, he integrated the different groups of the population and sharpened the democratic consciousness of the citizens of this still-fragile democracy.